1960
DOI: 10.6028/jres.064d.055
|View full text |Cite
|
Sign up to set email alerts
|

Computation and measurement of the fading rate of moon-reflected UHF signals

Abstract: A m ethod is d escribed for predict ing t he fast fa ding r ate of moon-reflected sig nals. It is b ase d entirely upon consid erations of t he observer-moon posit ions a nd r elative mo t ions. Exp erimental results which ar e in good agreement with t llC compu ted fad in g rates have been obtained from a moon-refl ection exp erim ent at a frequency of 4 12 m egacycles p et' second. So me possible implication s of t h is method of interpret ing fad ing r ates a re given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1960
1960
1963
1963

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It seems highly likely that there will be a wavelength dependence in the scattering cross section in view of the fact that the longer wavelengths penetrate more deeply into the surface layer before being reflected. However, the large scatter of the points shown in Figure 22 makes it unwise to infer such a dependence from the present results, and it is important to obtain a value for the cross section at a wavelength in the centimeter region which has an accuracy comparable with that at 1-meter wavelength obtained by Fricker et al [1960].…”
Section: Introduction the Relationship Between The Delay T And The Amentioning
confidence: 71%
See 1 more Smart Citation
“…It seems highly likely that there will be a wavelength dependence in the scattering cross section in view of the fact that the longer wavelengths penetrate more deeply into the surface layer before being reflected. However, the large scatter of the points shown in Figure 22 makes it unwise to infer such a dependence from the present results, and it is important to obtain a value for the cross section at a wavelength in the centimeter region which has an accuracy comparable with that at 1-meter wavelength obtained by Fricker et al [1960].…”
Section: Introduction the Relationship Between The Delay T And The Amentioning
confidence: 71%
“…If the value for pg obtained by Fricker et al [1960] at a wavelength of 73 cm, i.e., 7.4 per cent, is employed, together with the assumed values for g for the two components stated above, a value for the reflection coefi%ient (taken to be the same for both components) p = 0.064 is obtained. This yields a value for the dielectric constant/• = 2.8 close to that of dry terrestrial sand or pumice, but only about half the value observed for most silicate rocks, which average around/• = 5.…”
Section: Introduction the Relationship Between The Delay T And The Amentioning
confidence: 99%